Perceptual overview of the application of the Magic Towns Program in Jerez, Zacatecas (GEON Journal (Management, Organizations and Business), 2021)
Problematic: In 2007, Jerez joined the “Magic Towns” Program of the Tourism Department of the Federal Government, seeking a consequent increase in tourist activity; Objectives: The motivation to carry out this research is to characterize, from the perspective and opinion of local authorities, inhabitants, tourists and businesspeople, the benefits obtained; if they are perceptible to them. Materials and methods: Under a research methodology with a mixed approach, the field study collected data through surveys specifically designed for each population under study; such data treatment and analysis were carried out using statistical software. Results and Discussion: Derived from the analysis of the results, it can be determined that, according to the perception of the residents, businesspeople and authorities, there is not enough statistical information to ensure that the Magical Towns program of the Federal Government has promoted the development of Jerez. Conclusions: The research concludes that there are differences within the perceived benefits according to the study population in question, so the aspects in which there are perceptual differences should be considered to identify the strategies in which to place efforts. Contribution: In general, strategies that contribute to a better use of the Magic Town brand in that town are provided; still, above all, would have a positive impact on its social and economic development.
Keywords: brand; cultural tourism; economic and social development; local community; statitics; research; Z32 Development and Tourism; Z33 Marketing and Finance